BURNING ISSUES OF CRIMINAL LIABILITY FOR THE VIOLATION OF FIRE-SAFETY REGULATIONS - R. R. Fazylov (Russian Journal of Economics and Law, 2010)
Basing on the existing legal norms, researchers' views and statistical data, the author studies the novels of Article 219 of the Russian Criminal Code Violation of fire-safety regulations and the consequences caused by them, and grounds the author's interpretation of the main direct object of this crime.